2019
DOI: 10.3390/antiox8090414
|View full text |Cite
|
Sign up to set email alerts
|

Catalase-Like Antioxidant Activity is Unaltered in Hypochlorous Acid Oxidized Horse Heart Myoglobin

Abstract: Activated neutrophils release myeloperoxidase that produces the potent oxidant hypochlorous acid (HOCl). Exposure of the oxygen transport protein horse heart myoglobin (hhMb) to HOCl inhibits Iron III (Fe(III))-heme reduction by cytochrome b5 to oxygen-binding Iron II (Fe(II))Mb. Pathological concentrations of HOCl yielded myoglobin oxidation products of increased electrophoretic mobility and markedly different UV/Vis absorbance. Mass analysis indicated HOCl caused successive mass increases of 16 a.m.u., consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…This is supported by previous studies which have shown that HOCl induces modifications of several proteins resulting in loss of function of these proteins. For example, HOCl oxidatively modifies horse heart myoglobin in vitro and results in loss of reduction of myoglobin from the ferric to the ferrous state caused by cytochrome b5 reductase, an event essential for oxygen transport caused by myoglobin [ 9 ]. Furthermore, HOCl and another MPO oxidant—HOSCN—modify low density lipoprotein (LDL), thereby interfering with endothelial vasorelaxation and inducing endothelial dysfunction [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by previous studies which have shown that HOCl induces modifications of several proteins resulting in loss of function of these proteins. For example, HOCl oxidatively modifies horse heart myoglobin in vitro and results in loss of reduction of myoglobin from the ferric to the ferrous state caused by cytochrome b5 reductase, an event essential for oxygen transport caused by myoglobin [ 9 ]. Furthermore, HOCl and another MPO oxidant—HOSCN—modify low density lipoprotein (LDL), thereby interfering with endothelial vasorelaxation and inducing endothelial dysfunction [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidising HOCl also modifies thiol residues and many redox sensitive amino acids (cysteine, tyrosine, and methionine). For example, HOCl induces the chlorination of tyrosine residues, producing the biomarker 3-chlorotyrosine, which is used for quantification of HOCl-induced protein damage [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides NO, Mb also directly regulates ROS homeostasis, acting as both antioxidant and pro-oxidant. Mb exhibits catalase- and peroxidase-like activities thereby neutralizing the ROS-generating H 2 O 2 while itself being converted from ferric-heme to ferryl-heme Mb [ [167] , [168] , [169] , [170] ]. The role of Mb in cardiac antioxidant defense is observed in Mb knockout mice that show poor adaptation to oxidative challenge, including higher ROS in the heart upon cardiac I/R injury and slow recovery from ischemic insult [ 171 ].…”
Section: Myoglobinmentioning
confidence: 99%
“…In addition, mice infected with T. cruzi and exposed to NO donors are more protected against trypomastigotes compared to the control group [ 196 , 197 ]. Lastly, NO promotes splenocyte apoptosis during the acute phase of T. cruzi infection in mice [ 198 , 199 ] and modulates parasite cell entry, thus contributing to the pathogenesis of Chagas cardiomyopathy [ 188 , 200 , 201 , 202 ].…”
Section: Antiparasitic Effects Of No On Protozoa and Metazoamentioning
confidence: 99%